Enhancement of the double Higgs production via leptoquarks at the LHC - Da Rold, Leandro (2021)
Measurements of single Higgs production and its decays are in good agreement with the Standard Model. There is still room for large modifications in double Higgs production at LHC, though these effects may be correlated with large corrections to other observables, in particular single Higgs production. In this work we address the issue of enhancing double Higgs production in the presence of scalar leptoquarks while satisfying all experimental constraints. We show at leading order that including more than one species of leptoquarks, large cubic interactions with the Higgs can lead to sizable enhancement of di-Higgs production cross section at LHC, while at the same time keeping other Higgs observables and precision measurements under control. For masses above 800 GeV these corrections are in general below 30%, whereas in a viable scenario in which one of the leptoquarks can be light, specifically in the mass range 400-600 GeV, we show that it is possible to roughly double the SM cross section for di-Higgs production, implying that possible first hints of it may be probed at the high luminosity LHC at L ∼ 2 ab⁻¹.